(untitled) (Research, Society and Development, 2021)
This study analyzed the labeling of medications in Brazil based on the perception of health professionals and users in order to propose modifications and improvements that avoided the error of medication use. The qualitative approach was used to collect data, and the semi-structured interview technique was performed among health professionals and the focal group technique among the users. This collection took place throughout 2017. The main difficulties encountered by drug product respondents were similar labels, the difficulty of finding the items on the labels, the different information on the primary and secondary packaging of the medicines and the difficulty in visualizing information in the labels. And the suggestions were to remove the unnecessary information labels that are considered obvious; and adding or highlighting the dosage information area, the route of administration, the mode of preparation of the medicines and storage form for preservation. About the general modifications there was agreement on the definition of color of the label according to the pharmacological action of the drug and on the standardization in the increase of letter of the main information of the label.